Candidates of Genomic Tests in HR+/HER2- Breast Cancer Patients With 1-2 Positive Sentinel Lymph Node Without Axillary Lymph Node Dissection: Analysis From Multicentric Cohorts - Bi, Zhao; Chen, Jia-Jian; Liu, Peng-Chen; Chen, Peng; Wang, Wei-Li; Liu, Yan-Bing; Wang, Chun-Jian; Qiu, Peng-Fei; Lv, Qing; Wu, Jiong; Wang, Yong-Sheng (Frontiers in Oncology, 2021)
Background and purpose: The purpose was to construct a nomogram to predict precisely which HR+/HER2- patients with 1-2 positive sentinel lymph nodes (SLNs) could receive genomic tests. Methods: We conducted a retrospective analysis of 18,600 patients with stage I-III breast cancer patients treated with sentinel lymph node biopsy (SLNB) in multicentric cohorts. The logistic analysis was conducted to identify predictive factors of ≤ 3 positive axillary lymph nodes (ALNs) among HR+/HER2- patients with 1-2 positive SLNs. Then we built a nomogram, the discrimination of nomogram was evaluated by ROC curve. Results: Based on the database of the three institutions, a total of 18,600 breast cancer patients were identified undergoing SLNB between May 2010 and 2020. Among the 1817 HR+/HER2- patients with 1-2 positive SLNs undergoing ALND, 84.2% harbored ≤ 3 totals metastatic ALNs. The multivariate logistic regression analysis identified imaging abnormal nodes (OR=0.197, 95%CI: 0.082-0.472), the number of positive SLNs (OR=0.351, 95%CI: 0.266-0.464), the number of negative SLNs (OR=1.639, 95%CI: 1.465-1.833), pathological tumor stage (OR=0.730, 95%CI: 0.552-0.964), and lympho-vascular invasion (OR=0.287, 95%CI: 0.222-0.398) as independent predictors for the proportion of patients with ≤ 3 total metastatic ALNs (all p＜0.05). These five predictors were used to create a predictive nomogram. The AUC value was 0.804 (95％CI：0.681-0.812, p＜0.001). The calibration curve showed a satisfactory fit between the predictive and actual observation based on internal validation with a bootstrap resampling frequency of 1000. Conclusions: The nomogram showed good accuracy and could assist oncologist in determining precisely whose HR+/HER2- patients with 1-2 positive SLNs without ALND could perform genomic tests. In the era of SLNB and precision medicine, the combined application of genomic tests and SLNB could provide patients with a better strategy of dual de-escalation management, including the de-escalation of both surgery and systemic treatment.